Analysis of functionality in patients with post-COVID-19 pain: Functionality in patients with post-COVID-19 pain - Mesquita de Sousa, Leticia Emilly; da Silva Gomes, Larisse; Marinho Machado, Wysllana; Passos dos Santos, Thalyta Cibele; Weryka da Silva Santos, Pammela; Ahmad Hazime, Fuad; Antonio Kato da Silva, Baldomero (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: COVID-19, caused by the SARS-CoV-2 virus, resulted in millions of deaths and affected individuals indiscriminately. "Long COVID" presents persistent manifestations, such as pain, fatigue and cognitive problems. Objective: To analyze whether patients suffering from post-COVID-19 pain had an impact on their functionality. Methods: Cross-sectional observational study involving one hundred and three participants, between 18 and 59 years old, with post-COVID-19 pain complaints. A structured questionnaire, pain threshold assessment, dynamometry and functional capacity tests were applied. The Visual Analogue Scale (VAS) and post-COVID-19 functional status (PCFS) measured pain and functional status, respectively. Results: Data analysis showed a significant correlation between Visual Analogue Scale (VAS) and PCFS, dynamometry and lifting score. Age was statistically correlated with PCFS, with the score for sitting and standing, indicating worse performance in the activity of getting up with age. Conclusion: Post-COVID-19 musculoskeletal pain is linked to reduced functionality and muscle strength, compromising daily activities and quality of life. It can also be concluded that there is a need for preventive and rehabilitative strategies for persistent symptoms in post-COVID-19 patients.